Macromol. Chem. Phys. 11/2018. Issue 11 (4th June 2018) - Yan, Shijing; Zhong, Zhenxin; Li, Xiang‐Dan; Wen, Pushan; Zhang, Haining; Li, Lizhong; He, Rui; Zhang, Aiqing; Lee, Myong‐Hoon
Abstract : Front Cover : In article1800056, Xiang‐Dan Li and co‐workers demonstrate how photo‐crosslinking of polymer electrolyte membranes in hydrated states is helpful for preserving proton channels of membranes well, by comparison with those in the dehydrated state. Furthermore, crosslinked networks and the well‐reserved ion channels can greatly improve the physical properties of membranes with a minimal loss of proton conductivity.